Hepatitis Delta Virus RNA Replication - Chung-Hsin Tseng; Michael M. C. Lai (Viruses, 2009)
Hepatitis delta virus (HDV) is a distant relative of plant viroids in the animal world. Similar to plant viroids, HDV replicates its circular RNA genome using a double rolling-circle mechanism. Nevertheless, the production of hepatitis delta antigen (HDAg), which is indispensible for HDV replication, is a unique feature distinct from plant viroids, which do not encode any protein. Here the HDV RNA replication cycle is reviewed, with emphasis on the function of HDAg in modulating RNA replication and the nature of the enzyme involved.